2015
DOI: 10.1002/gcc.22257
|View full text |Cite
|
Sign up to set email alerts
|

Promoter DNA methylation is associated with KLF11 expression in epithelial ovarian cancer

Abstract: As a transforming growth factor-β (TGF-β)-inducible gene, the expression of Krüppel-like transcription factor 11 (KLF11) is altered in several types of cancer. In the current study, through using human 9K CpG island array, KLF11 was identified as one of hypermethylated genes in RAS-transformed ovarian T29H cells. Methylation of the KLF11 promoter was also observed in ovarian cancer tissue samples accompanied by significantly reduced KLF11 gene expression. Interestingly, the expression of SMAD2, SMAD3, and SMAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…A number of studies demonstrated that DNA methylation in gene promoters can suppress gene transcriptional activity and results in downregulated gene expression (Baubec et al., ; Hallberg et al., ; Wang et al., ). Our previous studies showed that mRNA expression of the SC protein FKBP6 is significantly lower in testes of cattle–yak than in testes of yak (Li et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrated that DNA methylation in gene promoters can suppress gene transcriptional activity and results in downregulated gene expression (Baubec et al., ; Hallberg et al., ; Wang et al., ). Our previous studies showed that mRNA expression of the SC protein FKBP6 is significantly lower in testes of cattle–yak than in testes of yak (Li et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…*p<0.05 and co-repressors [14,15]. In previous studies, KLF11 supported TGF-β signaling by terminating the smad7 loop and activating smad3; thus exerting anti-proliferative and pro-apoptotic functions in epithelial ovarian, pancreatic and liver cancer cells [17][18][19][20]. In the process of TGF-βinduced EMT, KLF11 significantly promoted hepatocellular carcinoma local invasion and distant metastasis by binding to the Smad7 promoter and suppressing transcription of Smad7 or directly up-regulating Smad2/3 expression [21,23].…”
Section: Discussionmentioning
confidence: 93%
“…KLF11 is a member of this family and contains three C 2 H 2 -type zinc fingers, 2 acids and 2 regions rich in proline at the carboxyl and amino terminals [16]. Previous studies have shown that KLF11 has significant influence on proliferation, differentiation and apoptosis in epithelial ovarian, pancreatic and liver cancer [17][18][19][20]. While KLF11 promotes local invasion and distant migration in the EMT process in hepatocellular carcinoma [21], its biological functions and relationship with EMT in gastric cancer are not clarified.…”
mentioning
confidence: 99%
“…They also investigated the methylation level between normal and tumor ovarian tissues in 31 Chinese patients. Compared with the normal samples, the overall methylation level was dramatically increased in the tumor tissues (P = 0.0001), and this significant difference was observed through all stages of the disease (G. Wang et al, 2015). In another study, Potapova et al demonstrated that epigenetic inactivation of KLF11 occurs in myelodysplastic syndrome.…”
Section: Discussionmentioning
confidence: 95%